Association between age and acetabulum morphological changes in dry bones in the Thai population - Khomkham, Pandaree; Chotecharnont, Worachot; Srinuan, Pawika; Suriyasathaporn, Jirath; Srisaikaew, Patcharaporn; Inchai, Chirapat; Mann, Robert; Mahakkanukrauh, Pasuk (Biomedical Sciences and Clinical Medicine, 2017)
Age estimation is one of the essential aspects of biological identi fi cation from human skeletal remains. The hip bone is often found at the scene and the acetabular region is usually one of the best preserved parts of the skeleton and can be of use in medico-legal examinations. Rissech (2) in 2006 identi fi ed seven features of the acetabulum which were found to be statistically signi fi cantly correlated with age at death. The present study investigated the correlation between those seven morphological features in the acetabulum and age in the Thai population. The study was performed using skeletal remains of 48 Thai individuals (34 males and 14 females). We found three of the seven features that were signi fi cantly statistically correlated with age at death: the left side of the acetabular groove in females (r = 0.61), acetabular rim porosity (r = 0.59) and apex activity score in left side male acetabulums (r = 0.62). This indicates that morphological changes of the acetabulum may be useful in estimating age at death in the Thai population when a hip bone is available for forensic examination